The effect of the TGF-β isoforms on progenitor cell recruitment and differentiation into cardiac and skeletal muscle - Schabort, Elske Jeanne (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Physiology (Human and animal))-- University of Stellenbosch, 2007.